Economic Evaluation and Systematic Review of Salt Marsh Restoration Projects at a Global Scale - Wang, Jiang-Jing; Li, Xiu-Zhen; Lin, Shi-Wei; Ma, Yu-Xi (Frontiers in Ecology and Evolution, 2022)
Restoring degraded and damaged salt marshes has become an important initiative in the coastal wetlands management around the world. Evaluating the distribution characteristics and economic output of salt marsh restoration is of great significance for identifying the current state of knowledge gaps related to conservation activities and economic benefits. To address this question, we conducted an overview of global salt marsh restoration projects, as well as their financial expenses and restoration benefits in the past 40 years. The results indicated that most of the saltmarsh restoration projects are near megacities and larger rivers, and restoration techniques of different regions depend on types of disturbance factors such as climate change, extreme weather events and land use change. With limited resources, fund allocation between protected areas and unprotected areas in middle income countries is often unbalanced , indicating mismatch between conservation efforts and regional needs. Although restoration projects are expensive, evidences in this article implies that most salt marsh restoration projects could recover their financial expense in the finite time, especially for large-scale restoration activities. Besides, the great carbon sequestration potential would make salt marsh restoration projects more profitable under current efforts to promote carbon sequestration for combating global warming.